Strategies for survival: The example of the clothing industry - Uwe Schwarting (Intereconomics, 1979)
In the debate about relocation to the developing countries of “structurally weak” industries the clothing industry has attracted the special interest of academic and political economists in the Federal Republic of Germany. The following article constitutes a summary of the most important findings of a study of the conditions under which this industry will be able to ensure its continuing existence in the Federal Republic in the future.
Keywords: 330; International Division of Labour